Performance of zinc oxide varistor discs sintered by alternative orientations - Karim, A.N. Mustafizul; Hashmi, M. S. J. (2005)
Processing of ZnO varistor discs undergoes several steps. Sintering is a major step for which electric kilns with a set temperature profile are commonly used. Cylindrical green compacts are placed vertically upon some ceramic tray called sagger. To prevent the contamination from the direct contact of the sagger, a liner material (made of ZnO) is used. The liner material is changed after a few cycles as it gets contaminated due to the exposure of high temperature reactions. Despite this change, the adverse effects arising out of the contact face of the disc cannot be avoided completely. Four orientations including the control were investigated to assess the extent of the undesirable effects. Apart from the control, the other three alternative orientations were Vee-groove support, thin sintered discs and green discs. Similar to the control, in the last two orientations the varistor discs were kept in vertical condition. Performance parameters such as energy absorption capability and high current behavior of the varistor discs were evaluated. Adverse effects due to the contact with liner materials were found to vary depending on the type of orientation. Some of these orientations have demonstrated superior performance of the varistor discs compared to the control.